2012
DOI: 10.1074/jbc.m112.349597
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Gephyrin in Hippocampal Neurons by Cyclin-dependent Kinase CDK5 at Ser-270 Is Dependent on Collybistin

Abstract: Background: Formation of inhibitory synapses in the CNS is dependent on cluster formation of the scaffold protein gephyrin. Results: Knockdown of collybistin and inhibition of cyclin-dependent kinases (CDK1,-2, and -5) abolished the phosphorylation of gephyrin detected by mAb7a at Ser-270. Conclusion: Gephyrin detected with mAb7a is phosphorylated at Ser-270. Significance: These data suggest a novel view on kinases involved in gephyrin phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 36 publications
10
76
0
3
Order By: Relevance
“…To test whether the identified short GABA A Rderived peptide fragments a9-11 also mediate binding to native full-length gephyrin comprising post-translational modifications, the peptides were covalently immobilized on iodoacetyl-activated beads and subsequently incubated with mouse brain lysates. In accordance with the recombinant GephE-based ITC results, a9-11 peptides, but not a8, could retain wild-type gephyrin on the beads, which was verified using the phosphospecific antibody mab7a 37 ( Fig. 2c and Supplementary Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…To test whether the identified short GABA A Rderived peptide fragments a9-11 also mediate binding to native full-length gephyrin comprising post-translational modifications, the peptides were covalently immobilized on iodoacetyl-activated beads and subsequently incubated with mouse brain lysates. In accordance with the recombinant GephE-based ITC results, a9-11 peptides, but not a8, could retain wild-type gephyrin on the beads, which was verified using the phosphospecific antibody mab7a 37 ( Fig. 2c and Supplementary Fig.…”
Section: Resultssupporting
confidence: 79%
“…After three washing steps with lysate buffer, the beads were boiled with Laemmli buffer containing 10% SDS. Subsequently, the supernatant was applied to an SDS-polyacrylamide gel electrophoresis followed by western blotting against gephyrin using the mAb7a antibody 37 (Synaptic Systems) at a dilution of 1:500.…”
Section: Methodsmentioning
confidence: 99%
“…However, gephyrin has been identified as a phosphoprotein when copurified with the GlyR (which has kinase activity), 40 and mass spectrometric analyses of rat and mouse brains revealed that gephyrin has 22 phosphorylation sites, most of which are located within the C domain (except for threonine 324, which lies in the E domain 25,[41][42][43] ) (Figure 1). These modifications might induce conformational changes by affecting the structure of the C domain or the neighboring G and E domains, thereby altering the clustering, trafficking and binding properties of gephyrin.…”
Section: Posttranslational Modificationsmentioning
confidence: 99%
“…In addition, cyclin-dependent kinase 5 mediates the collybistindependent phosphorylation of Ser270, suggesting that multiple signaling pathways converge at this residue of gephyrin. 42 It is less clear how gephyrin is dephosphorylated by phosphatases. Puzzlingly, one study showed that protein phosphatase 1 directly interacted with gephyrin and that gephyrin clustering was decreased by the application of broad-spectrum phosphatase inhibitors, 45 whereas two other studies conversely found that the dephosphorylation of gephyrin increased gephyrin clustering.…”
Section: Posttranslational Modificationsmentioning
confidence: 99%
“…Kuhse et al (2012) mostraram que a fosforilação de gefirina no resíduo de serina S270 é dependente tanto da ativação de proteínas quinases como GSK3β e CDK5 como da presença de colibistina. Ainda não se sabe ao certo os mecanismos pelos quais a fosforilação de gefirina no resíduo S270 contribuem para seu funcionamento em sinapses inibitórias, contudo os autores verificaram que mutações em gefirina em resíduos próximos ao S270, que impedem sua fosforilação, provocam alteração no tamanho de seus agrupamentos proteicos.…”
Section: Papel Da Colibistina No Funcionamento Das Sinapses Inibitóriunclassified